Analisis Erosi dan Sedimentasi di Sub Das Alo-Pohu Kesatuan Pengelolaan Hutan Vi Gorontalo - Mosi, Yetty; Warow, Novalia; Usman, Mutmainnah; Bahuwa, Isra Cahayani; Rosalia, Nurma; Kadir, Zein Setiawan; Hamidun, Marini Susanti; Lihawa, Fitryane; Dunggio, Iswan (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Gorontalo Province has topography in the form of lowlands to highlands which is shaped like a basin and most of Gorontalo Province is a water catchment area. One of the rivers with quite high sedimentation levels is the Alo River. To avoid more severe damage, technical conservation steps need to be taken, one of which is by building serial and continuous Check Dams. This research aims to determine erosion and sedimentation control and its effectiveness in the Alo watershed. The research method used was a direct survey method at the activity location, interviews with related agencies and people who were active at the location, then analysis was carried out. The stages begin with collecting primary data, secondary data. The data analysis used is using the Smith and Wischmeier (1978) equation known as the Universal Soil Loss Equation (USLE) A = R x K x LS x C x P. The results of the research show that the activities The construction of the Check Dam was carried out in 2021 by the Environment and Forestry Service of Gorontalo Province through KPH VI Gorontalo which is located in Buhu Village, Gorontalo Regency. The results of studies in the field show that the width of the Alo River is narrowing and experiencing shallowing, marked by the appearance of deltas at several points. On average, the width of the Alo river is only around 3-4 meters with a depth of around 10-15 cm. The conclusion of this research is 4. The Check Dam built by DLHK Gorontalo Province through KPH VI does not function well in dealing with erosion and sedimentation that enters the Alok River due to lack of maintenance and involvement of the local community. Keywords: Soil conservation, Water, Gorontalo.